MUET webinar & workshop 2021 / Nazima Versay Kudus ... [et. al] - Versay Kudus, Nazima; Affendy Lee, Noor Azli; Ramli, Syahirah; Ismail, Isma Noornisa (Academy of Language Studies, 2021)
English Language Club in collaboration with the Malaysian University English Test (MUET) Unit, Academy of Language Studies, UiTM Cawangan Pulau Pinang(UiTMCPP) organised a MUET webinar on three consecutive Fridays - 16, 23, and 30 April 2021 and a two-day workshop on 11 and 12 June 2021. Since the country is under lockdown due to COVID-19, the sessions were made possible on Google Meet. 80 students participated at the diploma level from the Permatang Pauh and Bertam campus